1968
DOI: 10.2466/pms.1968.26.2.563
|View full text |Cite
|
Sign up to set email alerts
|

Error, Response Time and IQ: Sex Differences in Cognitive Style of Preschool Children

Abstract: Reflectivity-impulsivity in response to task uncertainty has been suggested as an important cognitive style. The present study investigated response time (a measure of reflectivity-impulsivity), errors on a matching-figures task, and intelligence in preschool children. The results indicate that there are important and significant sex differences in preschool children's cognitive style: boys' errors were significantly correlated only with their response speed, while girls' errors only with their intelligence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
2

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 3 publications
1
18
2
Order By: Relevance
“…This accords with the postulated developmental trend for this dimension. The preschool sample used by Lewis, Rausch, Goldberg, and Dodd (1968) had lower error (mean = about 13) and faster time scores (about 3.8 seconds) than ours. However, their version of the MFF was much simpler, and their children were brighter.…”
Section: Discussioncontrasting
confidence: 46%
“…This accords with the postulated developmental trend for this dimension. The preschool sample used by Lewis, Rausch, Goldberg, and Dodd (1968) had lower error (mean = about 13) and faster time scores (about 3.8 seconds) than ours. However, their version of the MFF was much simpler, and their children were brighter.…”
Section: Discussioncontrasting
confidence: 46%
“…It was found that females were more reflective than males who were more impulsive. This confirmsfindings of Lewis, Rausch, Goldberg, and Dodd (1968), and Lewis (1971). However, it is in contrast with Messer's (1976) findings.…”
Section: Discussioncontrasting
confidence: 35%
“…Reflectivity or reflective style is the tendency tospend a comparably long time for making a decision or finding an answer to a problem, sometimes to consider all possibilities before making a decision. Lewis, Rausch, Goldberg, and Dodd (1968) concluded that boys were more impulsive than girls, and that their errors significantly correlated with their response speed. In a similar study by Lewis (1971) the same results were obtained.…”
Section: Literature Review Field Dependence/independencementioning
confidence: 99%
“…l 0h~) T her e ap p e a r s to be l i t t l e or no d i f f e r e n c e w i t h regard t o qender on the MFF , although studies reporting these data are not consistent or conclusive (Harrison & Nadelma n , 1972; Ka qan , lQ6 6 a ; Lewis , Rousch , Goldberg, & Dodd , 1971). When sex-linked differences were reported , it seems that girls may be somewhat more r e fl e ct i~~e than boys (Messer , 1976).…”
mentioning
confidence: 94%